2021
DOI: 10.1136/bmjsem-2020-000895
|View full text |Cite
|
Sign up to set email alerts
|

Do the combined blood pressure effects of exercise and antihypertensive medications add up to the sum of their parts? A systematic meta-review

Abstract: ObjectiveTo compare the blood pressure (BP) effects of exercise alone (EXalone), medication alone (MEDSalone) and combined (EX+MEDScombined) among adults with hypertension.Data sourcesPubMed, Scopus, Cumulative Index to Nursing and Allied Health Literature, SPORTDiscus and the Cochrane Library.Eligibility criteriaRandomised controlled trails (RCTs) or meta-analyses (MAs) of controlled trials that: (1) involved healthy adults>18 year with hypertension; (2) investigated exercise and BP; (3) reported preinterv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 70 publications
2
25
0
1
Order By: Relevance
“…Thus, our data dispel the speculation that AHM intake could prevent the effects of exercise-training on lowering BP. Furthermore, in agreement with a recent metanalysis [26], our data indicates that exercise may have similar effects on lowering BP regardless the use of antihypertensive medication in hypertensives patients with metabolic syndrome. Thus, exercise training lowers BP on those subjects with low responsiveness to medication (i. e., Med-Hyper, ▶ Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, our data dispel the speculation that AHM intake could prevent the effects of exercise-training on lowering BP. Furthermore, in agreement with a recent metanalysis [26], our data indicates that exercise may have similar effects on lowering BP regardless the use of antihypertensive medication in hypertensives patients with metabolic syndrome. Thus, exercise training lowers BP on those subjects with low responsiveness to medication (i. e., Med-Hyper, ▶ Fig.…”
Section: Discussionsupporting
confidence: 92%
“…As a subgroup analysis in their meta-review, Pescatello and colleagues (6) examined seven meta-analyses that compared the BP lowering effects of mind-body exercise combined with medication versus mind-body exercise alone or medication alone. They found strong evidence mind-body exercise combined with antihypertensive medication potentiated the BP lowering effects of medication alone (6). Similarly, in a network meta-analysis by Dai and colleagues (23) found Tai Chi and medication combined elicited greater SBP reductions by 12.4 mm Hg and DBP reductions by 7.6 mm Hg than medication alone (23).…”
Section: Late Breaking Newsmentioning
confidence: 99%
“…Indeed, although there is currently a paucity of data available with respect to the effect of exercise interventions on submaximal exercise BP, one randomized controlled study has shown significant reductions in systolic BP measured at stages 3 and 4 of a modified Bruce protocol compared to a non-exercise control group [ 62 ]. It is also pertinent that exercise training can provide reductions in BP that are equivalent to pharmacological intervention [ 63 ], with the BP-lowering effects of exercise training enhanced when combined with pharmacotherapy [ 64 ]. Exercise training that improves cardiorespiratory fitness should also lead to improved systolic BP for a given fixed submaximal workload and theoretically lessen the rate of increase in BP during incremental exercise testing (although this likely depends on the health status of the individual) [ 21 ].…”
Section: Intervenementioning
confidence: 99%